Metal Matrix Composites - Manoj Gupta (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Metal matrix composites are a unique class of materials capable of circumventing the disadvantages of each category of materials they are composed of (polymers, metals, and ceramics). They can be designed using at least two categories of materials, harnessing their useful properties according to the designated end applications. In view of the compositional flexibility inherently associated with metal matrix composites, new materials with enhanced properties can be synthesized from practically all the metallic materials that are currently utilized in engineering and biomedical applications. This book, comprising 20 peer-reviewed papers, addresses the recent developments in the designing, processing, characterization, and potential applications of metal-based composites. The research articles cover composites based on light-weight materials (Al, Mg, and Ti) and other metal-based materials (Cu, Ag, and W), such as matrices and reinforcements from nano-length scales (such as ZnO, SiC, Y2O3, CNTs, Sm2O3, graphene oxide) to macro-length scales (such as tungsten fiber nets, saffil fibers etc.). The focus was placed almost equally on solid-state, liquid-state and two-phase synthesis techniques. Similarly, the elastic, mechanical, and thermal properties of the described composites are reported in detail. This compilation of papers will certainly be most useful for students, industrial professionals, and academics interested in learning and expanding their knowledge on metal-based composites.